Persepsi Pemerintah Daerah terhadap Partisipasi Masyarakat dan Transparansi Akuntanbilitas Anggaran - Pudjiastuti, Irjani; Nurdhiana, Nurdhiana (Jurnal Ilmiah Aset, 2010)
The purpose of this research was to know the response of local government of Central Java Province to society participation and the transparency and accountability in compilation of APBD. Population in this research was all committee of Budget compiler which was consisted of 32 people, and sample taken by census, and also the data analysis method in this research by using scale of interval class. The result of this research indicated that perception of local government of Central Java Province to society participation in budget compilation in very good criterion with average of weight 29,50. and the perception of local government of Central Java Province to transparency and accountability related to compilation of APBD in criterion very good with average of weight 21,25. So that there by perception of Local Government of Central Java Province to society participation in compilation of budget and public policy transparency in budget compilation was very good, so that it can be conducted that people are active in participation of compilation of budget and activity of transparency and accountability has been very transparent and accountable.